Ninth Five Year Plan 1997-2002 Volume-XI Government of Assam - Planning Commission (Planning Commission, 1997)
An amount of Rs. 492.00 lakhs has been earmarked for implementation of various schemes during the annual plan of 1997-93. Out of this 121.61 lakhs is capital content. Moreover 226.78 lakhs has been proposed for Basic Minimum Service out of which 86.61 lakhs is for capital content (construction of buildings). It has been proposed to start the construction works of 10 nos. C.H.C. and 2 nos. of C.H.C. in both the Hills Districts during this year.
Development Commissioner for Hill Areas